Frequency of neoplasms in cats in the city of Lima during the period 1996-2007 - Castro D., Talía (2012)
The study aimed to determine the frequency of neoplasmas that were histopathologically diagnosed at the Pathology Laboratory of School of Veterinary Medicine, San Marcos University in the period 1996-2007. The retrospective study included 73 cases of neoplasms. Animals older than 9 years of age (49.3%) and females (72.9%) were the most affected. Tumors of epithelial origin were the most common type (53.5%), being mammary adenocarcinoma (21.1%) and lymphoma (16.9%) the most frequent.